Curable resin composition, cured product, laminate, non-slip pavement structure and method for producing the same
Patent Information
- Application Number
- JP2023135629
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
AI Technical Summary
【0008】 本発明の硬化性樹脂組成物は、塗装作業性に優れるうえ、骨材上に上塗り層を形成する硬化性樹脂組成物を塗布しない場合においても骨材が離脱しにくい硬化性樹脂組成物、前記硬化性樹脂組成物を硬化した硬化物、並びに前記硬化物を含む積層体および滑り止め舗装構造体を提供することができる。
Smart Images

Figure 2025030383000001 
Figure 2025030383000002 
Figure 2025030383000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition, a cured product obtained by curing the curable resin composition, a laminate and an anti-slip pavement structure containing the cured product, and a method for producing the anti-slip pavement structure. [Background technology]
[0002] 2. Description of the Related Art (Meth)acrylic curable resin compositions have excellent low-temperature curing properties, weather resistance, and chemical resistance, and therefore have been applied to floors, walls, road pavements, and the like, and then cured to be used as covering materials. For example, Patent Document 1 describes a resin composition containing at least one type of (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester polymer or copolymer, a plasticizer, and a compound having at least two polymerizable double bonds. The resin composition can be applied thickly and has no problem in practical use on roads, but the adhesion of the aggregate contained as an anti-slip material is insufficient, and it has been desired to improve the adhesion.
[0003] As an example of a coating layer having excellent durability such as strength and peel resistance and in which aggregate does not easily come off, Patent Document 2 describes a coating layer having a lower layer made of a hardened product of a syrup composition containing an acrylic monomer, a polymer soluble in the acrylic monomer, and a plasticizer, and an upper layer made of a hardened product of a syrup composition containing an acrylic monomer, a polymer soluble in the acrylic monomer, and a plasticizer, and containing aggregate near the boundary between the lower layer and the upper layer.
[0004] The covering layer described in Patent Document 2 is composed of a lower layer and an upper layer, and thus the amount of aggregate that breaks off is small. However, if the upper layer is not applied, the amount of aggregate that breaks off becomes large. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-96976 [Patent Document 2] JP 2008-207182 A Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above problems, the present invention aims to provide a curable resin composition that is excellent in coating workability and that prevents aggregate from falling off even when a curable resin composition for forming a topcoat layer is not applied to aggregate, a cured product obtained by curing the curable resin composition, a laminate and an anti-slip pavement structure containing the cured product, and a method for manufacturing an anti-slip pavement structure. [Means for solving the problem]
[0007] The present invention relates to the following items [1] to [9]. [1] A compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, a compound (B) which is an epoxy (meth)acrylate having two (meth)acryloyl groups, at least one polymer (C) selected from an acrylic polymer and a vinyl chloride-vinyl acetate copolymer, and a reducing agent (D), may contain a radical polymerizable compound (F) other than the compound (A) and the compound (B), A curable resin composition, wherein the proportion of the compound (B) with respect to the total of the compound (A), the compound (B), the polymer (C) and the radically polymerizable compound (F) is 14 to 45 mass %. [2] The curable resin composition according to [1], wherein the curable resin composition has a specific gravity of 1.0 to 1.3 at 23° C. as measured using a specific gravity cup. [3] The curable resin composition according to [1] or [2], wherein the polymer (C) is a vinyl chloride-vinyl acetate copolymer. [4] The curable resin composition according to [3], wherein the vinyl chloride content in the vinyl chloride-vinyl acetate copolymer is 50 to 89 mass %. [5] The curable resin composition according to any one of [1] to [4], wherein the viscosity of the curable resin composition measured at 23°C using a Brookfield viscometer at a rotation speed of 60 rpm is 1000 to 4500 mPa s. [6] A cured product obtained by curing the curable resin composition according to any one of [1] to [5]. [7] A laminate comprising the cured product according to [6]. [8] An anti-slip pavement structure comprising a hardened material layer containing the hardened material described in [6] and aggregate. [9] A method for producing an anti-slip pavement structure, comprising: applying a curable resin composition onto a road pavement surface, and scattering aggregate thereon to form a cured layer containing the curable resin composition and the aggregate, The curable resin composition includes a compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, a compound (B) which is an epoxy (meth)acrylate having two (meth)acryloyl groups, at least one polymer (C) selected from an acrylic polymer and a vinyl chloride-vinyl acetate copolymer, and a reducing agent (D), and may include a radical polymerizable compound (F) other than the compound (A) and the compound (B); A method for producing an anti-slip pavement structure, wherein the proportion of the compound (B) to the total of the compound (A), the compound (B), the polymer (C) and the radically polymerizable compound (F) is 14 to 45 mass%. Effect of the Invention
[0008] The curable resin composition of the present invention has excellent coating workability and is capable of providing a curable resin composition from which aggregate is less likely to come off even when a curable resin composition that forms a topcoat layer on aggregate is not applied, a cured product obtained by curing the curable resin composition, and a laminate and an anti-slip pavement structure each containing the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following definitions of terms apply throughout the specification and claims. "(Meth)acrylic" is a general term for acrylic and methacrylic. "(Meth)acrylate" is a general term for acrylate and methacrylate. The term "(meth)acryloyl group" is a general term for acryloyl groups and methacryloyl groups. "(Co)polymer" means a homopolymer or a copolymer. The symbol "~" indicating a range of numerical values means that the numerical values before and after it are included as the lower limit and upper limit.
[0010] <Curable resin composition> The curable resin composition of the present invention comprises a compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, an epoxy (meth)acrylate compound (B) having two (meth)acryloyl groups, at least one polymer (C) selected from an acrylic polymer and a vinyl chloride-vinyl acetate copolymer, and a reducing agent (D), and may comprise a radical polymerizable compound (F) other than the compounds (A) and (B), and the proportion of the compound (B) to the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F) is 14 to 45 mass%. Each component used in the present invention will now be described.
[0011] (Component A: Compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule) Component A used in the present invention is a compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, and is a component that improves the coating workability of the curable resin composition and improves the solubility of the polymer (C) described below. The alkyl group having 1 to 8 carbon atoms in compound (A) does not have a substituent.
[0012] From the viewpoints of flammability and coating workability, the number of carbon atoms in the alkyl group in compound (A) is preferably 3 or more, and more preferably 4 or more. On the other hand, from the viewpoints of the curability and surface hardness of the cured product, the number of carbon atoms in the alkyl group in compound (A) is preferably 6 or less, and more preferably 4 or less. Also, from the viewpoint of the curability of the cured product, a (meth)acrylic acid ester compound is preferred as compound (A).
[0013] Specific examples of the compound (A) include (meth)acrylic acid ester compounds having a linear alkyl group such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, and n-octyl (meth)acrylate; (meth)acrylic acid ester compounds having a branched alkyl group such as iso-propyl (meth)acrylate, iso-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and iso-octyl (meth)acrylate; and (meth)acrylic acid ester compounds having an aliphatic cyclic alkyl group such as cyclohexyl (meth)acrylate.
[0014] Among these, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, and t-butyl (meth)acrylate are preferred from the viewpoints of flammability, coating workability, and curing properties of the cured product. As the component A, one type of compound (A) may be used alone, or two or more types of compounds (A) may be used in combination.
[0015] (Component B: Compound (B) which is an epoxy (meth)acrylate having two (meth)acryloyl groups) The component B used in the present invention is a compound (B) that is an epoxy (meth)acrylate having two (meth)acryloyl groups in the molecule, and can adjust the viscosity and specific gravity of the curable resin composition. In addition, the cured product containing the component B can suppress the separation of aggregates.
[0016] The compound (B) can be obtained, for example, by reacting an epoxy resin with (meth)acrylic acid. Examples of the epoxy resin include bisphenol type epoxy resin, novolac type epoxy resin, aliphatic type epoxy resin, glycidyl ester type epoxy resin, and glycidyl amine type epoxy resin. Various epoxy resins such as solid and liquid types can be used. One type of epoxy resin may be used alone, or two or more types may be used in combination.
[0017] In the production of the compound (B), other monomers than (meth)acrylic acid may be used as necessary. The other monomers are not particularly limited as long as they are copolymerizable with (meth)acrylic acid, and examples thereof include (meth)acrylates having one (meth)acryloyl group in the molecule.
[0018] Examples of compound (B) include Etercure 6240 (manufactured by Choko Materials Industry Co., Ltd.), Etercure 620-100 (manufactured by Choko Materials Industry Co., Ltd.), Epoxy Ester 40EM(N) (manufactured by Kyoeisha Chemical Co., Ltd.), Miramer PE210 (manufactured by Bigen Specialty Chemical Co., Ltd.), and Miramer PE230 (manufactured by Bigen Specialty Chemical Co., Ltd.). As the component B, one type of compound (B) may be used alone, or two or more types of compounds (B) may be used in combination.
[0019] (Component C: At least one polymer (C) selected from acrylic polymers and vinyl chloride-vinyl acetate copolymers) The component C used in the present invention is at least one polymer (C) selected from an acrylic polymer (hereinafter also referred to as "polymer (C1)") and a vinyl chloride-vinyl acetate copolymer (hereinafter also referred to as "polymer (C2)"). The polymer (C) can adjust the viscosity and specific gravity of the curable resin composition. Furthermore, the curing time of the curable resin composition can be shortened. From the viewpoint of increasing the specific gravity of the curable resin composition, the polymer (C) is preferably the polymer (C2).
[0020] The polymer (C1) is a homopolymer or copolymer having a structural unit derived from a monomer having a (meth)acryloyl group. Examples of the polymer (C1) include a (meth)acrylic acid (co)polymer, a (meth)acrylate (co)polymer, a copolymer of (meth)acrylic acid and (meth)acrylate, and a (meth)acrylic polymer having a polymerizable double bond.
[0021] The (meth)acrylic acid (co)polymer is a homopolymer or copolymer having a structural unit derived from (meth)acrylic acid. Examples of the (meth)acrylic acid (co)polymer include a homopolymer of acrylic acid, a homopolymer of methacrylic acid, a copolymer of acrylic acid and methacrylic acid, and a copolymer of (meth)acrylic acid and other monomers (excluding (meth)acrylate). Examples of the other monomers include monomers having a vinyl group such as styrene, α-methylstyrene, acrylonitrile, and vinyl acetate. When using other monomers, two or more kinds may be used in combination.
[0022] The (meth)acrylate (co)polymer is a homopolymer or copolymer having a structural unit derived from (meth)acrylate. Examples of the (meth)acrylate (co)polymer include a (co)polymer obtained by polymerizing only one or more (meth)acrylates, and a copolymer of one or more (meth)acrylates and other monomers (excluding (meth)acrylic acid). Examples of the other monomers include vinyl group-containing monomers such as styrene, α-methylstyrene, acrylonitrile, and vinyl acetate. When using other monomers, two or more types may be used in combination.
[0023] Examples of the (meth)acrylate include the monofunctional (meth)acrylates exemplified in the description of the compound (A) and the radically polymerizable compound (F) described below.
[0024] The copolymer of (meth)acrylic acid and (meth)acrylate is a copolymer having a structural unit derived from the (meth)acrylic acid and a structural unit derived from the (meth)acrylate.
[0025] The (meth)acrylic polymer having a polymerizable double bond is a homopolymer or copolymer having a structural unit derived from a monomer having a (meth)acryloyl group and having a polymerizable double bond.
[0026] The polymer (C1) can be obtained by polymerizing these compounds (monomers) by various conventional methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. The weight average molecular weight of the polymer (C1) is preferably from 5,000 to 200,000, more preferably from 10,000 to 180,000. The weight average molecular weight means a value obtained by dissolving a polymer in a solvent (tetrahydrofuran), measuring the molecular weight by gel permeation chromatography (GPC), and converting the molecular weight into polystyrene equivalent.
[0027] The polymer (C2) is a vinyl chloride-vinyl acetate copolymer, that is, a copolymer resin in which vinyl chloride and vinyl acetate are copolymerized. From the viewpoints of solubility in the curable resin composition, viscosity, and coating workability, the vinyl chloride content in the vinyl chloride-vinyl acetate copolymer is preferably 50 to 89 mass %. That is, it is preferable that the vinyl acetate-derived structure is 11 to 50 mass % and the vinyl chloride monomer-derived structure is 50 to 89 mass % in the solid content (100 mass %) of the vinyl chloride-vinyl acetate copolymer.
[0028] The weight average molecular weight of the polymer (C2) is preferably from 5,000 to 200,000, and more preferably from 20,000 to 100,000, from the viewpoints of solubility in the curable resin composition, viscosity, and coating workability.
[0029] Examples of the compound (C2) include Solbin C5R (a copolymer of vinyl chloride / vinyl acetate (mass ratio) = 79 / 21, weight average molecular weight 58,000, manufactured by Nissin Chemical Industry Co., Ltd.), Solbin CL (a copolymer of vinyl chloride / vinyl acetate (mass ratio) = 86 / 14, weight average molecular weight 50,000, manufactured by Nissin Chemical Industry Co., Ltd.), Solbin C (a copolymer of vinyl chloride / vinyl acetate (mass ratio) = 87 / 13, weight average molecular weight 75,000, manufactured by Nissin Chemical Industry Co., Ltd.), VINNOL H40 / 43 (a copolymer of vinyl chloride / vinyl acetate (mass ratio) = 65.7 / 34.3, manufactured by Nissin Chemical Industry Co., Ltd.), and VINNOL H40 / 50 (a copolymer of vinyl chloride / vinyl acetate (mass ratio) = 63 / 37, manufactured by Nissin Chemical Industry Co., Ltd.). As the component C, one type of polymer (C) may be used alone, or two or more types of polymers (C) may be used in combination.
[0030] (Component F: radically polymerizable compound (F) other than compound (A) and compound (B)) The curable resin composition of the present invention may contain, as an optional component, a radically polymerizable compound (F) other than the compound (A) and the compound (B) as long as the desired effects are not impaired. The radical polymerizable compound (F) is not particularly limited as long as it is a compound having radical polymerizability. Specific examples of the radical polymerizable compound (F) include n-nonyl (meth)acrylate, iso-nonyl (meth)acrylate, n-decyl (meth)acrylate, iso-decyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, dicyclopentenyl (meth)acrylate, 2-dicyclopentenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, 2-dicyclopentenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentenyl (meth)acrylate. Ropentanyl (meth)acrylate, Adamantyl (meth)acrylate, Phenyl (meth)acrylate, Benzyl (meth)acrylate, Phenoxyethyl (meth)acrylate, Phenoxydiethylene glycol (meth)acrylate, Phenoxypolyethylene glycol (meth)acrylate, Nonylphenoxypolyethylene glycol (meth)acrylate, Phenoxypolypropylene glycol (meth)acrylate, Phenylphenyl (meth)acrylate, Phenylphenoxyethyl (meth)acrylate Acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, (1-naphthyl)methyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxypropyltriethoxysilane, p) hydroxyalkyl (meth)acrylates such as acryloyloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, (meth)acryloylmorpholine, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and glycerin mono(meth)acrylate;Examples of the hydroxy(meth)acrylate include hydroxy(meth)acrylates having a cyclic structure, such as hydroxyphenyl(meth)acrylate, hydroxycyclohexyl(meth)acrylate, hydroxynorbornyl(meth)acrylate, hydroxyisobornyl(meth)acrylate, hydroxydicyclopentenyl(meth)acrylate, hydroxydicyclopentanyl(meth)acrylate, hydroxyadamantyl(meth)acrylate, and 1,4-cyclohexanedimethanol mono(meth)acrylate.
[0031] The following polyfunctional (meth)acrylates can also be used as the radical polymerizable compound (F). Specifically, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, dibutylene glycol di(meth)acrylate, tributylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, biphenyl di(meth)acrylate, tert-butylene glycol ... Examples of the methacrylate include bifunctional (meth)acrylates such as bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, tricyclodecane di(meth)acrylate, dimethanol di(meth)acrylate, and polycarbonate diol di(meth)acrylate; trifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, and ε-caprolactone-modified tris((meth)acryloxyethyl)isocyanurate; tetrafunctional (meth)acrylates such as ditrimethylolpropane tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate.
[0032] Specific examples of the radical polymerizable compound (F) include vinyl group-containing monomers such as styrene, α-methylstyrene, acrylonitrile, and vinyl acetate, and compounds having an acryloyl group and a polybutadiene skeleton, a polyisoprene skeleton, a hydrogenated polybutadiene skeleton, or a hydrogenated polyisoprene skeleton. Examples of compounds having an acryloyl group and a polybutadiene skeleton, a polyisoprene skeleton, a hydrogenated polybutadiene skeleton, or a hydrogenated polyisoprene skeleton include 1,2-polybutadiene acrylate (trade name: NISSO-PB TE-2000, manufactured by Nippon Soda Co., Ltd.) and a hydrogenated 1,2-polybutadiene acrylate (trade name: NISSO-PB TEAI-1000, manufactured by Nippon Soda Co., Ltd.).
[0033] Other specific examples of the radically polymerizable compound (F) include urethane (meth)acrylates, polyester (meth)acrylates, and epoxy (meth)acrylates other than the compound (B).
[0034] The urethane (meth)acrylate as the radically polymerizable compound (F) can be obtained, for example, by reacting a polyol, a polyisocyanate, and a hydroxyl group-containing (meth)acrylate.
[0035] The polyol used to synthesize the urethane (meth)acrylate is a compound having two or more hydroxyl groups in one molecule. Examples of the polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polybutylene glycol, and polyhexamethylene glycol; addition reaction products of dihydric phenols such as bisphenol A, bisphenol F, and bisphenol S with alkylene oxides such as ethylene oxide and propylene oxide; and addition reaction products of polyhydric alcohols such as ethylene glycol, propylene glycol, butanediol, butylene glycol, and methylpentanediol with phthalic acid, isophthalic acid, and tetrahydrophthalic acid. polyester polyols obtained by reacting polybasic acids such as succinic acid, maleic acid, fumaric acid, adipic acid, sebacic acid, trimellitic acid, and the like, and their anhydrides; polylactone diols obtained from alkylene glycols and lactones; polycarbonate diols having carbonate bonds obtained by reacting diols such as butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, cyclohexanedimethanol, and the like, with carbonating agents such as phosgene and dimethyl carbonate, etc. These polyols may be used alone or in combination of two or more kinds.
[0036] The polyisocyanate used to synthesize the urethane (meth)acrylate is a compound having two or more isocyanate groups in one molecule. Examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, and isophorone diisocyanate. In addition, adduct compounds and trimer cyclized compounds of these compounds with water or trimethylolpropane can also be used as polyisocyanates. These polyisocyanates may be used alone or in combination of two or more.
[0037] Examples of hydroxyl group-containing (meth)acrylates used to synthesize urethane (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, an adduct of ε-caprolactone and 2-hydroxyethyl (meth)acrylate, etc. These hydroxyl group-containing (meth)acrylates may be used alone or in combination of two or more.
[0038] Also, if necessary, an allyl group-containing alcohol may be used instead of the hydroxyl group-containing (meth)acrylate. Examples of the allyl group-containing alcohol include allyl alcohol, ethylene glycol monoallyl ether, diethylene glycol monoallyl ether, polyethylene glycol monoallyl ether, propylene glycol monoallyl ether, dipropylene glycol monoallyl ether, polypropylene glycol monoallyl ether, glycerin monoallyl ether, glycerin diallyl ether, trimethylolpropane monoallyl ether, trimethylolpropane diallyl ether, pentaerythritol monoallyl ether, pentaerythritol diallyl ether, and pentaerythritol triallyl ether.
[0039] The polyester (meth)acrylate as the radical polymerizable compound (F) can be obtained, for example, by reacting a polybasic acid or its anhydride, a polyhydric alcohol compound, and (meth)acrylic acid or glycidyl (meth)acrylate by a known method. Examples of the polybasic acid include phthalic acid, isophthalic acid, tetrahydrophthalic acid, succinic acid, maleic acid, fumaric acid, adipic acid, etc. Examples of the polybasic acid anhydride include the anhydrides of the above polybasic acids. Examples of the polyhydric alcohol include ethylene glycol, propylene glycol, etc.
[0040] The epoxy (meth)acrylate other than the compound (B) as the radical polymerizable compound (F) can be obtained, for example, by the reaction of an epoxy resin with (meth)acrylic acid. Examples of the epoxy resin include bisphenol type epoxy resin, novolac type epoxy resin, aliphatic type epoxy resin, glycidyl ester type epoxy resin, and glycidyl amine type epoxy resin. Various epoxy resins, such as solid and liquid ones, can be used. One type of epoxy resin may be used alone, or two or more types may be used in combination.
[0041] The molecular weight of the urethane (meth)acrylate, the polyester (meth)acrylate, and the epoxy (meth)acrylate excluding the compound (B) is not particularly limited, but from the viewpoint of workability during coating, it is preferable that the weight average molecular weight is 30,000 or less. The weight average molecular weight means a value obtained by dissolving a polymer in a solvent (tetrahydrofuran), measuring the molecular weight by gel permeation chromatography (GPC), and converting the molecular weight into polystyrene equivalent.
[0042] (Reducing agent (D) and hardening agent (E)) The curable resin composition of the present invention can be cured by proceeding with a polymerization reaction by radicals generated from a redox polymerization initiator. The redox polymerization initiator is a polymerization initiator using a reducing agent (D) and a curing agent (E) in combination.
[0043] Examples of combinations of the reducing agent (D) and the curing agent (E) used in the redox-based polymerization initiator include the following (i) to (iv).
[0044] (i) A combination of an aromatic tertiary amine as a reducing agent (D) and dibenzoyl peroxide as a curing agent (E). Examples of aromatic tertiary amines include N,N-dimethyl-p-toluidine, N,N-diethylaniline, N,N-diethyl-p-toluidine, N-(2-hydroxyethyl)N-methyl-p-toluidine, N,N-di(2-hydroxyethyl)-p-toluidine, and N,N-di(2-hydroxypropyl)-p-toluidine. Furthermore, examples of aromatic tertiary amines include ethylene oxide or propylene oxide adducts of N,N-di(2-hydroxyethyl)-p-toluidine or N,N-di(2-hydroxypropyl)-p-toluidine. The aromatic tertiary amines are not limited to p (para) isomers, and may be o (ortho) or m (meta) isomers.
[0045] (ii) A combination of a metal soap as a reducing agent (D) and a hydroperoxide as a curing agent (E). Examples of metal soaps include cobalt naphthenate, copper naphthenate, manganese naphthenate, cobalt octoate, nickel octoate, cobalt acetylacetonate, zinc acetylacetonate, aluminum acetylacetonate, iron acetylacetonate, vanadyl acetylacetonate, and vanadium acetylacetonate.
[0046] Examples of hydroperoxides include cumene hydroperoxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-butyl hydroperoxide, t-hexyl hydroperoxide, t-amyl hydroperoxide, and 2,5-dimethylhexane-2,5-dihydroperoxide.
[0047] (iii) A combination of a thiourea compound as a reducing agent (D) and a hydroperoxide as a curing agent (E). Examples of the thiourea compound include thiourea, ethylenethiourea, N,N'-dimethylthiourea, N,N'-diethylthiourea, N,N'-dipropylthiourea, N,N'-di-n-butylthiourea, N,N'-dilaurylthiourea, N,N'-diphenylthiourea, trimethylthiourea, 1-acetyl-2-thiourea, and 1-benzoyl-2-thiourea. As the hydroperoxide, the same compounds as the hydroperoxides described in (ii) above can be used.
[0048] (iv) A combination of a thiourea compound as a reducing agent (D) and a monocarbonate-type peroxide as a curing agent (E). As the thiourea compound, the same compounds as the thiourea compounds described in the above (iii) can be used. Examples of monocarbonate type peroxides include t-hexylperoxyisopropyl monocarbonate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-butylperoxyallyl monocarbonate, and 1,6-bis(t-butylperoxycarbonyloxy)hexane.
[0049] The reducing agent (D) and the curing agent (E) may each be used alone or in combination of two or more kinds. As a combination of the reducing agent (D) and the curing agent (E), the combination (i) is preferred from the viewpoint of shortening the curing time of the curable resin composition and improving productivity. As the aromatic tertiary amine in the combination (i), N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-di(2-hydroxyethyl)-p-toluidine, and N,N-di(2-hydroxypropyl)-p-toluidine are preferred.
[0050] (Other ingredients) The curable resin composition of the present invention may further contain components (hereinafter also referred to as "other components") other than the above-mentioned compound (A), compound (B), polymer (C), radical polymerizable compound (F), reducing agent (D) and curing agent (E) as long as the desired effects are not impaired.
[0051] Examples of other components include paraffin wax, plasticizers, antioxidants, ultraviolet absorbers, thixotropic agents, defoamers, polymerization inhibitors, silane coupling agents, and other various additives, and radical polymerization initiators other than the curing agent (E) (such as thermal polymerization initiators and photopolymerization initiators).
[0052] To the curable resin composition of the present invention, paraffin wax may be added in order to suppress curing inhibition due to oxygen. The melting point of the paraffin wax is preferably 40 to 80° C. If the melting point is 40° C. or higher, sufficient air blocking effect is obtained when the curable resin composition is cured, and the surface curability is good. If the melting point is 80° C. or lower, the solubility of the paraffin wax is good when preparing the curable resin composition.
[0053] It is preferable to use two or more kinds of paraffin waxes with different melting points in combination. By using paraffin waxes with different melting points in combination, sufficient air blocking effect is obtained even when the temperature changes, and the surface curing property is good. When using paraffin waxes in combination, it is preferable to use paraffin waxes with a melting point difference of about 5 to 20°C.
[0054] As the paraffin wax, a wax dispersed in an organic solvent may be used in order to improve surface curability. The wax is dispersed in an organic solvent, and the dispersed wax is microparticulated to have a particle size of 0.1 to 50 μm, so that the air barrier effect can be effectively exhibited. Dispersed paraffin wax is commercially available, and the commercially available paraffin wax can be added as it is to the curable resin composition of the present invention.
[0055] Specific product names of paraffin wax include, for example, Paraffin 115 (trade name, melting point listed in the catalog: 47°C, manufactured by Nippon Seiro Co., Ltd.), Paraffin 130 (trade name, melting point listed in the catalog: 55°C, manufactured by Nippon Seiro Co., Ltd.), and Paraffin 150 (trade name, melting point listed in the catalog: 66°C, manufactured by Nippon Seiro Co., Ltd.).
[0056] A plasticizer may be added to the curable resin composition of the present invention in order to reduce shrinkage during curing. By adding a plasticizer, the blending ratios of compound (A) and compound (B) can be reduced, and shrinkage of the curable resin composition during curing can be reduced.
[0057] Examples of the plasticizer include phthalates such as dibutyl phthalate and di-2-ethylhexyl phthalate; adipic acids such as di-2-ethylhexyl adipate and octyl adipate; sebacates such as dibutyl sebacate and di-2-ethylhexyl sebacate; azelaic acids such as di-2-ethylhexyl azelate and octyl azelate; cyclohexane dicarboxylates such as 1,2-cyclohexane dicarboxylate diisopentyl ester and 1,2-cyclohexane dicarboxylate diisononyl ester; and paraffins such as chlorinated paraffins (excluding the paraffin waxes). The plasticizers may be used alone or in combination of two or more.
[0058] The curable resin composition of the present invention may contain an antioxidant to prevent oxidation deterioration of the cured product. Examples of the antioxidant include phenol-based antioxidants such as n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate and tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane; phosphorus-based antioxidants such as triphenyl phosphite and trisisodecyl phosphite; and sulfur-based antioxidants such as dihexyl sulfide, dilauryl-3,3'-thiodipropionate and ditridecyl-3,3'-thiodipropionate. The antioxidant may be used alone or in combination of two or more.
[0059] The curable resin composition of the present invention may contain an ultraviolet absorber to suppress photodegradation of the cured product. Examples of ultraviolet absorbers include derivatives of 2-hydroxybenzophenone such as 2-hydroxy-4-methoxybenzophenone and 2-hydroxy-octyloxybenzophenone; 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-ditertiarybutylphenyl)benzotriazole, or halides thereof; and phenyl salicylates such as phenyl salicylate and p-tertiarybutylphenyl salicylate. The ultraviolet absorber may be used alone or in combination of two or more kinds.
[0060] A thixotropic agent may be added to the curable resin composition of the present invention. Examples of the thixotropic agent include organic thixotropic agents such as urethane urea-based thixotropic agents, fatty acid amides, and organic bentonite; and inorganic thixotropic agents such as fine silica particles. The thixotropic agent may be used alone or in combination of two or more.
[0061] The curable resin composition of the present invention may contain a defoaming agent in order to remove bubbles in the curable resin composition. Examples of the defoaming agent include an acrylic defoaming agent obtained by dissolving an acrylic polymer in a solvent, and a vinyl defoaming agent obtained by dissolving a vinyl polymer in a solvent.
[0062] Specific product names of the defoaming agent include, for example, the Disparlon series manufactured by Kusumoto Chemical Industries, Ltd., which are OX-880EF, OX-881, OX-883, OX-8040, 1922, 1927, P-410EF, P-420, P-425, PD-7, 1970, 230, 230HF, and LF-1982; and BYK-052 and BYK-1752 manufactured by BYK Japan Co., Ltd. One type of defoaming agent may be used alone, or two or more types may be used in combination.
[0063] In order to improve storage stability, a polymerization inhibitor may be added to the curable resin composition of the present invention. Examples of the polymerization inhibitor include hydroquinone, 2-methylhydroquinone, hydroquinone monomethyl ether, and 2,6-di-t-butyl-4-methylphenol. The polymerization inhibitor may be used alone or in combination of two or more kinds.
[0064] A silane coupling agent may be added to the curable resin composition of the present invention in order to improve adhesion to a substrate such as asphalt or concrete. Examples of the silane coupling agent include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(glycidoxypropyl)trimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane. The silane coupling agent may be used alone or in combination of two or more.
[0065] The curable resin composition of the present invention may contain a thermal polymerization initiator to improve the curability. Examples of the thermal polymerization initiator include known peroxides and azo compounds. The curable resin composition of the present invention may contain a known photopolymerization initiator to improve the curability. These polymerization initiators may be used alone or in combination of two or more.
[0066] The curable resin composition of the present invention may contain a pigment for coloring. Examples of the pigment include organic pigments (azo pigments, phthalocyanine pigments, etc.) and inorganic pigments (ceramic pigments, iron oxide, titanium oxide, etc.). The pigments may be used alone or in combination of two or more.
[0067] [Amount of each ingredient] The content of the compound (A) in the curable resin composition of the present invention is preferably 20 to 80 mass%, more preferably 35 to 75 mass%, and even more preferably 45 to 65 mass%, based on the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F). The higher the content of the compound (A), the better the viscosity of the curable resin composition and the better the coating workability. The lower the content of the compound (A), the better the curability of the curable resin composition and the better the cured product can be obtained.
[0068] The content of the compound (B) in the curable resin composition of the present invention is 14 to 45% by mass based on the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F). If the content of the compound (B) is 14% by mass or more, the viscosity and specific gravity of the curable resin composition can be adjusted, and the separation of aggregate from the cured product can be suppressed. If the content of the compound (B) is 45% by mass or less, the viscosity of the curable resin composition does not become too high, and the workability during coating can be improved. The content of the compound (B) is preferably 15 to 35% by mass, more preferably 15 to 30% by mass.
[0069] The content of the polymer (C) in the curable resin composition of the present invention is preferably 5 to 40 mass% based on the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F), more preferably 10 to 35 mass%, and even more preferably 20 to 30 mass%. The higher the content of the polymer (C), the higher the specific gravity of the curable resin composition can be, and the shorter the curing time of the curable resin composition can be. The lower the content of the polymer (C), the lower the viscosity of the curable resin composition tends to be.
[0070] The content of the reducing agent (D) in the curable resin composition of the present invention is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F). From the viewpoint of the balance between the curability, the pot life and the workability, the content of the reducing agent (D) is more preferably 0.2 to 5 parts by mass, and further preferably 0.3 to 3 parts by mass, relative to the total of 100 parts by mass. The higher the content of the reducing agent (D), the better the curability of the curable resin composition. In addition, the lower the content of the reducing agent (D), the longer the gelation time of the curable resin composition, and the easier it is to stir the curable resin composition.
[0071] The amount of the curing agent (E) added to the curable resin composition of the present invention is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass, based on 100 parts by mass of the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F). The more the amount of the curing agent (E) added, the better the curability of the curable resin composition. In addition, the less the content of the curing agent (E), the longer the gelation time of the curable resin composition, making it easier to stir the curable resin composition.
[0072] [Method for producing curable resin composition] The curable resin composition of the present invention can be produced by mixing and stirring the above-mentioned components using a commonly used stirrer.
[0073] [Viscosity of Curable Resin Composition] The viscosity of the curable resin composition of the present invention, measured at 23° C. and a rotation speed of 60 rpm using a Brookfield viscometer, is preferably 500 to 6000 mPa s, more preferably 1000 to 4500 mPa s, and even more preferably 1500 to 4000 mPa s. When the viscosity of the curable resin composition is within the above range, the workability during coating is good.
[0074] [Specific gravity of curable resin composition] The specific gravity of the curable resin composition of the present invention is preferably 1.0 to 1.3, more preferably 1.0 to 1.2, as measured using a specific gravity cup at 23° C. By making the specific gravity of the curable resin composition 1.0 to 1.3, the quality standard described in the resin-based anti-slip pavement guidelines (2004 edition) established by the Resin Pavement Technology Association can be satisfied, and the composition can be suitably used as a curable resin composition for forming an anti-slip pavement structure described later.
[0075] [Method for obtaining a cured product of a curable resin composition] The following method is preferred as a method for curing the curable resin composition of the present invention to obtain a cured product. That is, first, the compound (A), the compound (B), the polymer (C), and the reducing agent (D), as well as other components (radical polymerizable compound (F), other components) are mixed together as necessary to prepare a curable resin composition containing no curing agent. Then, just before obtaining a cured product of this curable resin composition, the curing agent (E) is added and mixed into the curable resin composition containing no curing agent to initiate a polymerization reaction and obtain a cured product.
[0076] Means for applying the curable resin composition of the present invention include known application methods using a roller, a metal trowel, a brush, a flexible broom, a coating machine (such as a spray coating machine), and the like. From the viewpoint of workability, the temperature during application of the curable resin composition is preferably from -30°C to 60°C, and more preferably from -10°C to 40°C. The polymerization time for curing the curable resin composition is preferably 10 to 300 minutes. When the polymerization time is 10 minutes or more, good coating workability of the curable resin composition can be obtained, and when it is 300 minutes or less, the total coating work time can be shortened. The polymerization time can be adjusted by adjusting the blending amounts of the reducing agent (D) and the curing agent (E) according to the temperature during coating.
[0077] After the coating operation involving a polymerization reaction is completed, curing is preferably performed. The curing temperature is preferably -10°C to 65°C, more preferably 0°C to 60°C, and even more preferably 5°C to 50°C. By setting the curing temperature at -10°C to 65°C, the polymerization reaction of the curable resin composition progresses sufficiently, and the properties of the cured product become good. The curing time varies depending on the curing temperature, but is preferably 10 minutes to 24 hours.
[0078] In order to suppress bubbles in the cured product, the curable resin composition may be subjected to vacuum degassing, vibration degassing, or the like after the curing agent is blended with the curable resin composition.
[0079] [Uses of the curable resin composition] The applications of the curable resin composition of the present invention include, for example, paints, casting materials, binders, adhesives, repair materials, and joint materials.
[0080] Examples of paints include road paints: anti-slip paints, drainage paints, heat-shielding paints, road marking paints, and floor slab waterproofing paints. Civil engineering and construction paints: wall paints, floor paints, roof paints, bridge paints, plant paints, steel structure paints, and concrete paints. Furniture paints, decorative paints, electronic device paints, mobile device paints, home appliance paints, waterproof paints, automobile paints, motorcycle paints, heavy machinery paints, railroad car paints, and marine paints.
[0081] Examples of molded articles obtained when used as a casting material include films, sheets, lenses, optical waveguides, and sealing materials. The molded articles are used in, for example, light-emitting diode modules, mobile phones, smartphones, tablet terminals, personal computers, cameras, organic electroluminescence (organic EL) devices, flat panel displays, touch panels, electronic paper, photodiodes, phototransistors, solar cells, and projectors. The molded articles can also be used as optical components.
[0082] Examples of the binder material include binders for artificial marble, fiber reinforced plastics, braille tiles, and the like. Examples of adhesives include glass adhesives, resin adhesives, metal adhesives, and second generation acrylic adhesives (SGA). Examples of the repair material include concrete repair materials and road repair materials. Examples of the joint material include tile joint material, stone joint material, concrete joint material, and asphalt joint material.
[0083] Among these applications, the applications of the curable resin composition of the present invention are preferably road paints, civil engineering and construction paints, repair materials, joint materials, etc., more preferably road paints, and even more preferably anti-slip paints.
[0084] [Laminate] The laminate of the present invention is a laminate containing a cured product of the curable resin composition of the present invention, and can be suitably used as a laminate for civil engineering and construction in civil engineering and construction applications such as road paints, civil engineering and construction paints, repair materials, and joint materials. The laminate for civil engineering and construction use of the present invention can be used as a covering material for floor surfaces such as asphalt or concrete, wall surfaces, and road pavement surfaces. The cured product of the curable resin composition of the present invention can be used, for example, as a coating layer formed directly on the surface to be applied, as at least one layer when a laminate including at least two layers, an undercoat layer and a topcoat layer, is formed on the surface to be applied, or as at least one layer when a laminate including at least three layers, an undercoat layer, an intermediate coat layer and a topcoat layer, is formed on the surface to be applied. In particular, the cured product of the curable resin composition of the present invention is suitable for use as an undercoat layer or an intermediate coat layer, since it causes little detachment of aggregate, which will be described later.
[0085] <Anti-slip pavement structure> In this embodiment, the anti-slip pavement structure refers to a pavement structure in which a curable resin composition as a binder is thinly and uniformly applied to a road pavement surface such as asphalt or concrete pavement, and then aggregate, which will be described later, is scattered on the cured resin composition to form a cured layer that is fixed to the road surface. A curable resin composition that forms a topcoat layer may be applied on the cured resin layer.
[0086] The hardened layer contains aggregate, which can impart anti-slip properties. Specific examples of aggregate include sand, silica sand, river sand, kansui stone, emery, marble, calcium carbonate, kaolin, bentonite, mica, talc, silicon carbide powder, silicon nitride powder, boron nitride powder, alumina, slag, glass powder, ceramic aggregate, pottery waste, and colored aggregate. These aggregates may be used alone or in combination of two or more.
[0087] The particle size of the aggregate depends on the thickness of the hardened layer, but is preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less, as determined by sieving. When the particle size of the aggregate is 5 mm or less, flexibility is easily obtained for the anti-slip pavement structure.
[0088] <Method of manufacturing anti-slip pavement structure> The anti-slip pavement structure of this embodiment is intended for road pavement surfaces, particularly asphalt and concrete pavement surfaces, and can be produced by coating these surfaces. The method for manufacturing an anti-slip pavement structure includes a step of applying a curable resin composition used in civil engineering and construction onto a road pavement surface, and then scattering aggregate thereon to form a hardened layer containing the curable resin composition and the aggregate.
[0089] For example, the curable resin composition of the present invention is first applied to a road pavement surface, and then aggregate is spread before gelation. The thickness of the curable resin composition applied to the road pavement surface is preferably 0.5 mm to 2 mm, more preferably 1 mm to 1.8 mm. If the applied thickness is too thin, the curability decreases and the amount of aggregate detached tends to increase, and if the applied thickness is too thick, the cost increases. The aggregate is spread by hand or using a spreader in excess so that the curable resin composition cannot be seen, and the excess aggregate is collected after the curable resin composition has hardened. If necessary, a curable resin composition for forming a topcoat layer may be applied on the cured product layer to form a topcoat layer.
[0090] Examples of a means for applying the curable resin composition include known application methods using a roller, a metal trowel, a brush, a flexible broom, a coating machine (such as a spray coating machine), and the like. From the viewpoint of workability, the temperature during application of the curable resin composition is preferably -30°C to 60°C, more preferably -10°C to 40°C, and the curing time is preferably in the range of 20 minutes to 60 minutes. When the curing time is 20 minutes or more, good coating workability and gripping properties of the curable resin composition on aggregates can be obtained, and when it is 60 minutes or less, good adhesion to asphalt or concrete pavement surfaces, which are road pavement surfaces, can be obtained.
[0091] The aggregate remaining rate when the anti-slip pavement structure is subjected to the below-described stationary cutting test is preferably 90% or more, and more preferably 91% or more. When the aggregate remaining rate is 90% or more, there is little detachment of anti-slip aggregate, and the structure can be suitably used as an anti-slip pavement structure. EXAMPLES
[0092] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In each example and comparative example, "parts" means "parts by mass".
[0093] [Synthesis Example 1: Synthesis of (meth)acrylic polymer (polymer 1)] In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 135 parts of deionized water and 0.4 parts of polyvinyl alcohol (saponification degree 80 mol%, polymerization degree 1700) as a dispersant were added and stirred until the polyvinyl alcohol was completely dissolved, after which the stirring was stopped. 60 parts of methyl methacrylate, 40 parts of n-butyl methacrylate, 0.2 parts of 2,2'-azobis-2-methylbutyronitrile as a polymerization initiator, 0.8 parts of n-dodecyl mercaptan as a chain transfer agent, and 0.1 parts of sodium carbonate as an electrolyte were added and stirred again, and the mixture was heated to 75°C and reacted for 2.5 hours. The mixture was further heated to 98°C and maintained for 1.5 hours, after which the reaction was terminated. After cooling to 40°C, the resulting aqueous suspension was filtered through a nylon filter cloth with 45 μm mesh, and the filtrate was washed with deionized water, dehydrated, and then dried at 40°C for 16 hours to obtain a granular (meth)acrylic polymer (polymer 1). The resulting (meth)acrylic polymer (Polymer 1) had a glass transition temperature (Tg) of 65° C. and a weight average molecular weight of 42,000.
[0094] [Synthesis Example 2: Synthesis of (meth)acrylic polymer (polymer 2)] Except for changing the amount of n-dodecyl mercaptan used from 0.8 parts to 0.5 parts, a granular acrylic polymer (polymer 2) was obtained in the same manner as in Synthesis Example 1. The glass transition temperature (Tg) of the obtained granular (meth)acrylic polymer (polymer 2) was 65° C., and the weight average molecular weight was 160,000.
[0095] [Example 1] Into a 1 L flask equipped with a stirrer, a thermometer, and a cooling tube, 61 parts of n-butyl methacrylate as compound (A), 16 parts of bifunctional epoxy acrylate (manufactured by Choko Materials Industry Co., Ltd., trade name: Etercure 6240) as compound (B), 0.4 parts of N,N-di(2-hydroxyethyl)-p-toluidine as reducing agent (D), and 0.5 parts of paraffin 115 (manufactured by Nippon Seiro Co., Ltd.), 0.4 parts of paraffin 130 (manufactured by Nippon Seiro Co., Ltd.), 0.3 parts of paraffin 150 (manufactured by Nippon Seiro Co., Ltd.), 0.5 parts of defoamer (manufactured by Kusumoto Chemical Industry Co., Ltd., trade name: Disparlon 230EF), and 0.02 parts of hydroquinone monomethyl ether were added, and then, with stirring, 23 parts of vinyl chloride-vinyl acetate copolymer (manufactured by Nissin Chemical Industry Co., Ltd., trade name: Solvine C5R) as polymer (C) was added. Subsequently, the mixture was heated at 60° C. for 2 hours with stirring to dissolve the mixture. After confirming that the solid content had been dissolved, the mixture was cooled to 40° C. to obtain a resin composition (S-1). Table 1 shows the composition of the obtained resin composition (S-1).
[0096] [Examples 2 to 9, Comparative Examples 1 to 4] Resin compositions (S-2) to (S-13) were obtained in the same manner as in the preparation of resin composition (S-1), except that the blending compositions were changed as shown in Tables 1 to 3.
[0097] The abbreviations in Tables 1 to 3 are as follows. n-BMA: n-butyl methacrylate MMA: Methyl methacrylate 2-EHA: 2-Ethylhexyl acrylate Etercure 6240: Bifunctional epoxy acrylate (manufactured by Choko Materials Industries Co., Ltd.) 40EM: Bifunctional epoxy methacrylate (product name: Epoxy Ester 40EM(N), manufactured by Kyoeisha Chemical Co., Ltd.) PE-210: Bifunctional epoxy acrylate (product name: MiramerPE210, manufactured by Bigen Specialty Chemical Co., Ltd.) PE-230: Bifunctional epoxy acrylate (product name: MiramerPE230, manufactured by Bigen Specialty Chemical Co., Ltd.) Solvine C5R: A copolymer of vinyl chloride / vinyl acetate (mass ratio) = 79 / 21, with a weight average molecular weight of 58,000 (manufactured by Nissin Chemical Industry Co., Ltd.) Solvin CL: A copolymer of vinyl chloride / vinyl acetate (mass ratio) = 86 / 14, with a weight average molecular weight of 50,000 (manufactured by Nissin Chemical Industry Co., Ltd.) VINNOL H40 / 43: A copolymer of vinyl chloride / vinyl acetate (mass ratio) = 65.7 / 34.3 (manufactured by Nissin Chemical Industry Co., Ltd.) Polymer 1: A copolymer of MMA / n-BMA (mass ratio) = 60 / 40 produced in Synthesis Example 1, with a weight average molecular weight of 42,000 Polymer 2: A copolymer of MMA / n-BMA (mass ratio) = 60 / 40 produced in Synthesis Example 2, with a weight average molecular weight of 160,000 PDE-150: Triethylene glycol dimethacrylate (product name: Blenmer PDE-150, manufactured by NOF Corporation) BPE-4: EO modified bisphenol A diacrylate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) M-600A: 2-hydroxy-3-phenoxypropyl acrylate (product name: Epoxy Ester M600A, manufactured by Kyoeisha Chemical Co., Ltd.) SUA-017: Bifunctional urethane acrylate with a number average molecular weight of 6,300 (manufactured by Asia Industries Co., Ltd.) PTEO: N,N-di(2-hydroxyethyl)-p-toluidine (manufactured by Nippon Nyukazai Co., Ltd.) Paraffin 115: Paraffin wax (product name: Paraffin 115, manufactured by Nippon Seiro Co., Ltd.) Paraffin 130: Paraffin wax (product name: Paraffin 130, manufactured by Nippon Seiro Co., Ltd.) Paraffin 150: Paraffin wax (product name: Paraffin 150, manufactured by Nippon Seiro Co., Ltd.) Disparlon 230EF: Defoamer (product name: Disparlon 230EF, manufactured by Kusumoto Chemicals Co., Ltd.) BYK-1752: Defoamer (product name: BYK-1752, manufactured by BYK Japan Co., Ltd.) Adeka Cizer P300: Adipic acid polyester plasticizer (manufactured by ADEKA Corporation) MEHQ: Hydroquinone monomethyl ether HQ: Hydroquinone
[0098] (Weight average molecular weight) The polymer was dissolved in a solvent, tetrahydrofuran, and the molecular weight was measured by gel permeation chromatography, and the weight average molecular weight was calculated in terms of polystyrene.
[0099] (viscosity) The liquid temperature of the curable resin composition was set to 23° C., and the viscosity was measured using a Brookfield viscometer at a rotation speed of 60 rpm.
[0100] (specific gravity) The liquid temperature of the curable resin composition was set to 23° C., and the specific gravity at 23° C. was measured using a specific gravity cup.
[0101] <Evaluation of Coating Workability of Curable Resin Composition> One side of a 300 mm x 300 mm x 60 mm concrete slab (manufactured by Yuko Shokai Co., Ltd.) specified in JIS A 5371:2016 "Precast unreinforced concrete products" was ground with a disc grinder to remove laitance. After the shavings on the ground surface were brushed off, 2 parts of benzoyl peroxide (trade name: Perkadox GB-50L, manufactured by Kayaku Nouryon Co., Ltd., purity 50%) were added to 100 parts of resin composition (S-1) and mixed in a room at a temperature of 23°C, and the resulting curable resin composition was applied with a trowel at a rate of 1.9 kg / m. 2 The paint workability when the resin composition was applied to a concrete plate so as to obtain a paint composition having a thickness of 100 mm or more was evaluated based on the following evaluation criteria. The resin compositions (S-2) to (S-13) were also evaluated in the same manner. The results are shown in Tables 1 to 3.
[0102] (Evaluation Criteria) ○: The curable resin composition is easy to smooth with a trowel and does not become stringy. △: The curable resin composition is difficult to smooth with a trowel, but no stringiness occurs. ×: The curable resin composition is difficult to smooth with a trowel, and stringiness occurs.
[0103] <Preparation of Laminate> Using the curable resin compositions obtained in the Examples and Comparative Examples, laminates were produced by the following method. One side of a 300 mm x 300 mm x 60 mm concrete slab (manufactured by Yuko Shokai Co., Ltd.) specified in JIS A 5371:2016 "Precast unreinforced concrete products" was ground with a disc grinder to remove laitance. After the shavings on the ground surface were brushed off, 2 parts of benzoyl peroxide (trade name: Perkadox GB-50L, manufactured by Kayaku Nouryon Co., Ltd., purity 50%) were added to 100 parts of resin composition (S-1) and mixed in a room at a temperature of 23°C, and the obtained curable resin composition was applied with a trowel at a rate of 1.9 kg / m. 2 Immediately afterwards, 470 g of anti-slip aggregate (Cerasand A1 grain, particle size 2-3.3 mm, manufactured by Bishu Kosan Co., Ltd.) was spread over it, and after curing for 2 hours, the unattached aggregate was removed to form a laminate. The aggregate remaining rate of the obtained laminate was evaluated as follows.
[0104] <Evaluation of aggregate remaining rate> Using a tire stand-and-turn tester (manufactured by Intesco Co., Ltd.), the laminates obtained in the examples and comparative examples were used as test specimens, which were attached to the tire stand-and-turn tester 4 hours after preparation, and stand-and-turn tests were performed under the following conditions to measure the aggregate remaining ratio in the stand-and-turn area. The results are shown in Tables 1 to 3.
[0105] (Test conditions) Test specimen drive method: Test specimen repeat angle: ±30° Repetition speed: 6rpm Load: 3KN Measurement temperature: 23℃ Number of turns: 10 round trips
[0106] (Evaluation method) The residual aggregate rate after the test was calculated as a percentage by subtracting the weight difference of the laminate before and after the test from the initial aggregate amount, and dividing the result by the initial aggregate amount, as shown in the following formula: The initial aggregate amount is the amount of aggregate scattered when the laminate was made minus the amount of aggregate that did not adhere after curing. Aggregate remaining rate (%)={W1-(W2-W3) / W1}×100 W1: Initial aggregate amount (g) W2: Weight of the laminate before the suspension test (g) W3: Weight of the laminate after the suspension test (g)
[0107] [Table 1]
[0108] [Table 2]
[0109] [Table 3]
[0110] As shown in Tables 1 to 3, the curable resin compositions according to Examples 1 to 9 had a ratio of compound (B) to the total of compound (A), compound (B), polymer (C) and radical polymerizable compound (F) of 14 to 45% by mass, had a specific gravity of 1.0 to 1.3, and had good paint workability when applied with a trowel. In addition, the laminates containing the cured products had excellent aggregate residual ratios. In contrast, the curable resin compositions of Comparative Examples 1 to 4, which did not contain the compound (B), had low aggregate residual ratios in the laminates containing the cured products thereof. Furthermore, the curable resin compositions of Comparative Examples 1, 2, and 4 also had poor coating workability.
Claims
1. The present invention comprises a compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, a compound (B) which is an epoxy (meth)acrylate having two (meth)acryloyl groups, at least one polymer (C) selected from an acrylic polymer and a vinyl chloride-vinyl acetate copolymer, and a reducing agent (D), may contain a radical polymerizable compound (F) other than the compound (A) and the compound (B), The curable resin composition, wherein the ratio of the compound (B) to the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F) is 14 to 45 mass%.
2. The curable resin composition according to claim 1, wherein the specific gravity of the curable resin composition measured using a specific gravity cup at 23°C is 1.0 to 1.
3.
3. The curable resin composition according to claim 1, wherein the polymer (C) is a vinyl chloride-vinyl acetate copolymer.
4. The curable resin composition according to claim 3, wherein the vinyl chloride content in the vinyl chloride-vinyl acetate copolymer is 50 to 89 mass %.
5. 3. The curable resin composition according to claim 1, wherein the viscosity of the curable resin composition measured at 23° C. and a rotation speed of 60 rpm using a Brookfield viscometer is 1000 to 4500 mPa·s.
6. A cured product obtained by curing the curable resin composition according to claim 1 or 2.
7. A laminate comprising the cured product according to claim 6.
8. An anti-slip pavement structure comprising a hardened material layer comprising the hardened material according to claim 6 and aggregate.
9. A method for producing an anti-slip pavement structure, comprising: applying a curable resin composition onto a road pavement surface, and scattering aggregate thereon to form a cured layer containing the curable resin composition and the aggregate, The curable resin composition includes a compound (A) having an alkyl group having 1 to 8 carbon atoms and a (meth)acryloyl group in the molecule, a compound (B) which is an epoxy (meth)acrylate having two (meth)acryloyl groups, at least one polymer (C) selected from an acrylic polymer and a vinyl chloride-vinyl acetate copolymer, and a reducing agent (D), and may include a radical polymerizable compound (F) other than the compound (A) and the compound (B); A method for producing an anti-slip pavement structure, wherein the ratio of the compound (B) to the total of the compound (A), the compound (B), the polymer (C) and the radical polymerizable compound (F) is 14 to 45 mass%.
Citation Information
Patent Citations
Resin composition for marking material
JP1992096976A
Coated layer and method of forming the same
JP2008207182A